Sheet Metal 2009 - Shirvani, Bez; Duflou, Joost R.; Merklein, Marion; Micari, Fabrizio; Griffiths, Benjamin J.; et al. (Trans Tech Publications, 2009)
Volume is indexed by Thomson Reuters CPCI-S (WoS). Collections of peer-reviewed papers are always excellent sources of knowledge and new ideas for researchers working in both universities and industry. The present collection, in particular, provides interdisciplinary and international resources; thus encouraging the close cooperation of materials scientists, and manufacturing and computer engineers and promoting the diffusion of research results, and technology transfer, in all areas of Sheet Metal Processing and Characterizatio